Pendampingan Belajar Bahasa Arab dengan Metode CTL untuk Meningkatkan Mufrodat Siswa Kelas VI di MI BAITUL MUKMIN Wringinagung Jombang Jember - Furoidah, Asni; Ilma, Falashifatul (An-Nuqthah, 2024)
In learning activities, especially learning Arabic, appropriate methods and strategies are needed to achieve learning objectives. In this case the researcher tried to provide full assistance to class VI students at MI Baitul Mukmin Wringinagung Jombang Kencong in improving their mufrodat using the contextual teaching and learning (CTL) method. This assisted activity aims to emphasize the process of full student involvement in learning so that students can find the material being studied and relate it to daily life situations or certain fields, so that students can feel the meaning of each lesson material received and can implement it in their learning. various aspects of life. In this assisted activity, researchers used the PAR (Participatory Action Research) assisted method. The impact resulting from the use of the contextual teaching and learning (CTL) method applied to class VI students at MI Baitul Mukmin can improve their Arabic understanding, which initially had very little insight into Arabic language understanding.